HYDROCHEMICAL STUDY OF BALAK RIVER, ERBIL-IRAQ - Arkhawan J. Sh.,; R. N. Dara,; M.A. Chnaray,; A. R. Ahmed,; H.S. Khoshnaw, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to assess the water quality of different water resources (Surface water, subsurface in water, and groundwater) across the Balak river basin. Twenty two different water resource samples were collected and subjecting to a comprehensive physicochemical analysis. Balak river basin, situated in Erbil governorate, Iraq, it is located 10 km to the east from Bekhal Waterfall. Five attributers combine with Balak River within the basin areas which are: Rezanok Sub River, Balakiyan Sub River, Basan Sub River, Roste Sub River, and Alana Sub River. The hydro chemical study of all water resources during the investigated period revealed that the spring waters are relatively higher in electrical conductivity value compared to other sources. Some surface water samples were recorded high turbidity value. Values recorded for physicochemical parameters were within WHO and Iraqi standards guideline values except for some samples of turbidity. According to water classification, all samples have a very similar composition, and can be classified as Ca-HCO3 water. This indicated that they correspond to different sampling points along different rivers, and different samples along the same river.